2018
DOI: 10.3390/ijerph15122881
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep Quality in the Psychological Well-Being of Final Year UndergraduateStudents in China

Abstract: There are increasing numbers of university students in China suffering from poor sleep and psychological well-being problems. In particular, the issues are more severe among the final year undergraduate students, because they are experiencing a transitory period from university life to the workplace. However, extant research has rarely explored sleep quality and psychological well-being of final year university students. To better understand the role of sleep quality in psychological well-being, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 49 publications
(67 reference statements)
5
28
0
1
Order By: Relevance
“…Our analysis, however, revealed that sleep duration has a positive association with psychological well-being, a result that is consistent with the findings of Richter (2015). Similarly, just as Zhai et al (2018) found a strong relationship between sleep quality and psychological well-being, our univariate analysis showed that sleep efficiency and overall sleep quality are significantly and positively correlated with the same. Our multivariate analysis nevertheless informs that the positive association between overall sleep quality and psychological well-being is only true for above average levels of the latter.…”
Section: Sleep and Psychological Well-beingsupporting
confidence: 89%
See 2 more Smart Citations
“…Our analysis, however, revealed that sleep duration has a positive association with psychological well-being, a result that is consistent with the findings of Richter (2015). Similarly, just as Zhai et al (2018) found a strong relationship between sleep quality and psychological well-being, our univariate analysis showed that sleep efficiency and overall sleep quality are significantly and positively correlated with the same. Our multivariate analysis nevertheless informs that the positive association between overall sleep quality and psychological well-being is only true for above average levels of the latter.…”
Section: Sleep and Psychological Well-beingsupporting
confidence: 89%
“…Problems in their sleep environment may include noise and roommates’ different habits ( Qin and Brown, 2017 ). The demands to contribute to the communal life of the hall and to integrate socially in its high-density living environment ( Zhai et al, 2018 ), the stress from short-term academic workload and long-term anxiety related to independent adult life ( Lemma et al, 2012 ; Laidlaw et al, 2016 ), and the lack of knowledge and practice of good sleep hygiene ( Suen et al, 2010 ; Dinis and Braganca, 2018 ), further add to these problems. Not surprisingly, university students are viewed as being chronically sleep-deprived ( Curcio et al, 2006 ; Fonseca and Genzel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer sleep duration has been associated with positive affect, environmental mastery, personal growth, positive relations with others, purpose in life and self-acceptance [ 27 , 36 ], all of which have conceptual equivalence with the three PMH sub-components associated with sleep duration in our study. It is proposed that ‘feeling well rested’ due to adequate and better sleep could yield a more energetic self, capable of reaching personal goals and being socially connected with others [ 27 , 37 ]. Our findings, thus, provide support to the favourable association between sleep duration, sleep quality and mental health…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study also observed the socio-demographic and health characteristics of respondents, as these may affect their experiences and perceptions of metal health. In this study, the socio-demographic covariates were age [34], gender, monthly living expenses [12], educational level [35,36], place of birth [37], and subjects studied at undergraduate level. Moreover, the study controlled for the self-rated health of respondents and whether they had any instrumental daily living activities and/or limitations in relation to these activities, because prior research has indicated that these factors affect perceptions of mental health and well-being [38].…”
Section: Datamentioning
confidence: 99%